Big C: Taking the fight beyond drugs - Abd Razak, Dzulkifli (2005)
THE Prime Minister’s recent call to heighten the fight against cancer cannot be more timely. According to the 1st International Cancer Control Congress held in Vancouver from Oct 23 to 26, a few days after the demise of Datin Seri Endon Mahmood, more than six million people die of cancer worldwide each year – or more than 10 per cent of deaths reported globally. This makes cancer the second leading cause of death. With more than 20 million others living with cancer, the DirectorGeneral of World Health Organisation (WHO) refers to it as a "growing health crisis". In other words, it is a human, social or economic challenge for every nation, from a disease that is largely preventable. And, for Malaysia, it is no exception. In fact, by 2020, the year when Malaysia is to be a fully developed country, it is estimated that there will be 16 million new cases every year.